Rapid post-eruptive maturation of porcine enamel - Depalle, Baptiste; Karaaslan, Hakan; Obtel, Nicolas; Gil-Bona, Ana; Teichmann, Maren; Mascarin, Gabrielle; Pugach-Gordon, Megan; Bidlack, Felicitas B. (Frontiers in Physiology, 2023)
The teeth of humans and pigs are similar in size, shape, and enamel thickness. While the formation of human primary incisor crowns takes about 8 months, domestic pigs form their teeth within a much shorter time. Piglets are born after 114 days of gestation with some of their teeth erupted that must after weaning meet the mechanical demands of their omnivorous diet without failure. We asked whether this short mineralization time before tooth eruption is combined with a post-eruptive mineralization process, how fast this process occurs, and how much the enamel hardens after eruption. To address this question, we investigated the properties of porcine teeth at two, four, and sixteen weeks after birth (N = 3 animals per time point) through analyses of composition, microstructure, and microhardness. We collected data at three standardized horizontal planes across the tooth crown to determine the change of properties throughout the enamel thickness and in relation to soft tissue eruption. Our findings indicate that porcine teeth erupt hypomineralized compared to healthy human enamel and reach a hardness that is similar to healthy human enamel within less than 4 weeks.